KAJIAN LIFE CYCLE ASSESSMENT (LCA): ANALISIS CRADLE TO GATE PERTANIAN JAGUNG PAKAN DI KELOMPOK TANI DESA BAJUIN, KABUPATEN TANAH LAUT - Muhammad Indra Darmawan; Adzani Ghani Ilmannafian; Mariatul Kiptiah (EnviroScienteae, 2021)
The development of field corn farming in Indonesia continues to increase. Along with this, the potential risk, especially in environmental aspects, will be even greater. In this research, a study will be carried out using a Life Cycle Assessment (LCA) to obtain data on Greenhouse Gas (GHG) emissions and energy consumption in field corn farming at the farmer group level. The scope of research is limited to the analysis from land preparation to yielding harvested maize. The purpose of this study was to identify and measure the largest GHG and energy consumption in each process flow of field corn farming in order to design efficient mitigation efforts. The research method used in this research is field research in Bajuin. Data analysis refers to the SNI ISO 14040: 2016 Framework, which consists of 4 stages, namely (a) goal and scope definition, (b) life cycle inventory analysis, (c) life cycle impact assessment, and (d) life cycle interpretation. Life cycle inventory uses energy coefficients, emission factors, and the Intergovernmental Panel Climate Change (IPCC) guidelines. The results showed that the Total Global Warming Potential (GWP 100) in the production of 1 ton of shelled corn was 52605,277 Kg CO2 eq. The largest GHG emitted was in urea fertilization, with emissions of 81.35% of the total emissions. The amount of energy used in producing 1 ton of shelled corn is 5155 MJ, where the most significant energy recorded was the urea fertilization stage of 3592,600 MJ. A recommended efforts to reduce GHG emissions are the use of organic fertilizer substitutes for urea.